Three‐dimensional DEM Study of Coal Distribution in the Melter Gasifier of COREX. Issue 11 (13th May 2016) - You, Yang; Hou, Qin‐Fu; Luo, Zhi‐Guo; Li, Hai‐Feng; Zhou, Heng; Chen, Ren; Zou, Zong‐Shu
Abstract : COREX is one of the commercialized smelting reduction ironmaking processes. It mainly includes two reactors: a reduction shaft and a melter gasifier (MG). Lump coal is used in the MG to generate reducing agents, and hence its distribution plays an important role in determining the temperature distribution and the reduction of iron ores. To understand the formation of burden profiles, a three‐dimensional discrete element method (DEM) model is established and validated against experimental tests. The effects of key operational parameters such as the chute angle and the rotational speed are investigated, and the underlying mechanisms in the formation of an asymmetrical pile are analyzed. The results show that the asymmetrical pile is intrinsic to the discharge system due to the outward motion of lump coal. The results also reveal a significant size segregation of lump coal along the radial direction. Small particles tend to accumulate in the inner side of the pile while the large ones have large fractions in the outer side. The effect of the rotational speed is minor within the range from 3 to 12 rpm. These findings are helpful for the control and optimization of the MG to improve its energy efficiency. Abstract : A three‐dimensional discrete element method model is established and validated for studying the coal distribution in a COREX melter gasifier. First, the effects of chute angle and rotational speed are examined. Second, the formation of an asymmetrical burden pile and the underlying mechanisms are analyzed. Last, particle size segregation and velocity distribution are investigated.